Factors of Direct Provision of Goods and Services: The Role of the Environmental and Cleaning Service in Waste Bank Management in Pangandaran Regency - Rohaeni, Heni; Etih Henriyani; Eet Saeful Hidayat (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract This study aims to analyze the role of the Department of Environment and Sanitation in waste bank management in Pangandaran Regency. This study focuses on the weak role of the government, as indicated by the suboptimal provision of goods and services to support the waste bank program and the suboptimal provision of training in waste bank program management. The research design used a descriptive qualitative approach. The data sources used were primary data with seven informants. Data collection was conducted through structured interviews, participant observation, and documentation studies. Data analysis utilized data reduction, data presentation, and conclusion drawing. The results indicate that the government's role in providing goods and services and training remains suboptimal due to budget constraints, a lack of competent human resources, and the uneven distribution of supporting facilities. Conversely, supervision and control have been carried out routinely through reporting mechanisms. These findings confirm that an active role for local governments in directly providing facilities and infrastructure is essential to ensure the sustainability of the waste bank program and increase the effectiveness of community-based waste management in rapidly developing tourist areas. Keywords: Role of Government, Waste Bank, Department of Environment